Case Report : Diagnosis dan Tatalaksanan Pasien Perempuan 40 Tahun dengan Karsinoma Nasofaring di Rumah Sakit Cut Meutia Aceh Utara - Faiza Ardianti; Rahmi Surayya (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Nasopharyngeal Carcinoma (NPC) is a squamous cell carcinoma (SCC) originating from the nasopharyngeal epithelium. In Indonesia, NPC is the 4th most common malignancy after breast cancer, cervical cancer, and lung cancer. A 40-year-old woman came to the Emergency Room of Cut Meutia Hospital with complaints of left-sided nosebleeds for approximately 2 weeks before entering the hospital. The results of the physical examination found hair that was easily pulled out, then from the results of the supporting examination in the form of a non-contrast head CT-Scan, an expansion of the mass in the nasopharynx was found. Based on the anamnesis, physical examination and supporting examinations, the patient was diagnosed with nasopharyngeal carcinoma. The management that can be given to patients is non-drug, namely consuming nutritious food, and managing stress and sleep patterns, in addition the patient is also given symptomatic management.